Prospects for X-Ray and FUV Observations to Provide Insight Into the “Cepheid Mass Problem” - Evans, Nancy Remage; Engle, Scott (Frontiers in Astronomy and Space Sciences, 2019)
The classical Cepheid Leavitt Law (Period-Luminosity relation) has been known for 100 years, and used in extragalactic distance determination for nearly as long. Cepheids are particularly important in testing the inferences of asteroseismology, and the comparison of masses inferred from pulsation calculations, evolutionary calculations, and observationally measured masses is termed the “Cepheid mass problem.” However, Cepheids still present us with surprises. Recent results about X-ray behavior of δ Cep is one example. At minimum radius the pulsation wave from the envelope creates a disruption in the photosphere and chromosphere. X-ray activity, on the other hand remains constant at a low level at this phase. Just after maximum radius, however, X-ray flux increases sharply (4-fold in the case of δ Cep). We summarize here the observational program to explore parameters involved and theoretical investigations searching for a basic understanding of this upper atmosphere phenomenon. This results in new diagnostics of the linkages between the pulsating envelope, the upper atmosphere, and possible mass-loss in the system.